Why Is Food Cheaper in Rich (European) Countries? - Leon Podkaminer (The Vienna Institute for International Economic Studies (wiiw), 2005)
Relative to non-food items, food tends to be cheaper in rich, as compared with poor European countries. This tendency cannot be explained in terms of cost developments or foreign-trade considerations. A positive explanation proposed focuses on demand-income-supply interaction. An analysis of a cross-country price-augmented modification of Engel's Law, econometrically specified, indicates that the relative price of food is related positively to the supply of food items and negatively to that of non-food items. This finding is consistent with agricultural price scissors' and also casts a different light on the nature of economic development and structural change.
Keywords: O14; D12; D51; 330; relative prices; structural change; cross-country demand functions; demand for food